Bluetongue Virus Infections in Cattle Herds of Manabí Province of Ecuador - Euclides De la Torre (MDPI AG, 2021)
Bluetongue (BT) is a viral disease transmitted by Culicoides (Diptera: Ceratopogonidae) to domestic and wild ruminants. Infections in cattle are mainly subclinical, but severe necrotic and hemorrhagic illness and death may occur depending on the strain of the virus and other factors; cattle act as a reservoir for the virus. Although the Ecuadorian coast has climatic conditions that favor the presence of the vector, there are few serologic or virologic BTV studies available. Manabí is a coastal province in which livestock farming is mostly implemented in the northern part. We conducted two studies to assess, for the first time, the presence of active BTV infections in Manabí province. We collected 430 serum samples from 38 randomly selected farms between March and July 2019 to perform BTV competitive ELISA. In addition, six seropositive farms were selected to place eight sentinel BTV-naive calves. All these calves were blood sampled and the presence of BTV RNA and antibodies was tested for by RT-PCR and competitive ELISA, respectively, once a week for 6–8 weeks until seroconversion was evidenced. A high individual seroprevalence (99%) was obtained, and all investigated farms had BTV seropositive animals. All sentinel calves became BTV viremic and seroconverted. The first viremia appeared after 2–5 weeks from arrival at the farm; they seroconverted 1–3 weeks later. We demonstrate for the first time that there is a high level of BTV circulation north of Manabí, with active infections on these farms. Integrated control strategies such as hygienic measures on farms to reduce midge populations would be advisable for the owners as mitigation measures.